Efficacy of Microbials as Insecticides for the Management of Tomato (Lycopersicon esculentum) Fruitworm, Helicoverpa armigera (Hubner) - Rahman, AKMZ; Haque, MA; Alam, SN; Dutta, NK (The Agriculturists, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The experiment was conducted at the experimental field of Entomology Division, BARI, Gazipur during Rabi 2007-08. Two microbial insecticides HaNPV @ 0.4ml/L and Bt @ 2g/L along with their combination were tested against H. armigera. The lowest fruit infestation, both in number and weight, was obtained from treatment HaNPV and Bt alternate spraying (11.78%, 9.64%), followed by Bt (13.25%, 10.85%) and HaNPV (17.67%, 13.11%). The highest fruit yield (16.92 t/ha) was obtained from HaNPV and Bt alternate spraying plots followed by Bt (16.65 t/ha) and HaNPV (14.73 t/ha). In case of MBCR, the highest MBCR was obtained from HaNPV and Bt alternate spraying (5.30) followed by HaNPV (4.46) and Bt (3.37). DOI: http://dx.doi.org/10.3329/agric.v12i1.19583 <span style="font-size: 12.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Agriculturists <span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2014<span style="font-size: 12.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">; 1<span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2(1) 68-74<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>